Molecular Detection of CRISPR-Cas System in Staphylococcus epidermidis Isolated from Different Sources in Iraq - Thuraya Hashosh et al (Basrah Journal of Veterinary Research)
The goal of the present study was to isolate and identify (CRISPR-Cas) elements in S. epidermidis (MRSE) from 300 samples collected from various sources. Culture techniques, biochemical tests and VITEK2 system were used for confirming of Staphylococcus epidermidis isolation.  The partial sequencing of the 16s rRNA gene was evaluated and compared with those in the Gene Bank to find differences in the sequence using the BLAST tool (http://www.ncbi.nlm.nih.gov).  On the other hand, the CRISPR-Cas system was examined in all isolates of multidrug-resistant S. epidermidis in which the SECR1 and SECR2 elements were not found. The cas6 element was found in all of the tested bacterial strains. Susceptibility tests were done using the disc diffusion method after identification. Antibiotic resistance testing on S. epidermidis isolates revealed the highest percentage of multi-resistance to ampicillin, ceftriaxone, chloramphenicol, cefalexin, vancomycin, nalidixic acid at 100%. Moreover, S. epidermidis isolates showed intermediate effect against amoxillin-clavulanic acid, tobramycin, neomycin, oxacillin, tetracycline and methicillin. However, S. epidermidis isolates were found to be the most sensitive to erythromycin, norfloxacin and rifampicin. The CRISPR-Cas system can be found in S. epidermidis isolates from a variety of local sources and that the appearance of the CRISPR system in S. epidermidis isolates plays a unique role in antibiotic suitability.